2012
DOI: 10.1016/j.ajpath.2012.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of P-Glycoprotein and Doxorubicin Chemoresistance of Metastatic Breast Cancer Is Regulated by miR-298

Abstract: MicroRNAs (miRNAs) are short, noncoding RNA molecules that regulate the expression of a number of genes involved in cancer; therefore, they offer great diagnostic and therapeutic targets. We have developed doxorubicin-resistant and -sensitive metastatic human breast cancer cell lines (MDA-MB-231) to study the chemoresistant mechanisms regulated by miRNAs. We found that doxorubicin localized exclusively to the cytoplasm and was unable to reach the nuclei of resistant tumor cells because of the increased nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
169
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(184 citation statements)
references
References 33 publications
9
169
3
3
Order By: Relevance
“…17 MicroRNAs have been reported previously to induce chemo resistance of cancer cells by different mechanisms such as modulation of intracellular drug concentrations, modulation of drug target, enhancement of drug metabolism, inhibition of apoptosis, regulation of angiogenesis and generation of tumor stem cells. [18][19][20][21][22][23] Among the 14 miRNAs dysregulated in the present study in A549DOX11 cells, 4 (has-miR-1973, 494, 4286 and 29b-3p) have shown the highest level of upregulation (2.99 -4.44 folds) compared with the A549 parental cells.…”
Section: Discussionmentioning
confidence: 87%
“…17 MicroRNAs have been reported previously to induce chemo resistance of cancer cells by different mechanisms such as modulation of intracellular drug concentrations, modulation of drug target, enhancement of drug metabolism, inhibition of apoptosis, regulation of angiogenesis and generation of tumor stem cells. [18][19][20][21][22][23] Among the 14 miRNAs dysregulated in the present study in A549DOX11 cells, 4 (has-miR-1973, 494, 4286 and 29b-3p) have shown the highest level of upregulation (2.99 -4.44 folds) compared with the A549 parental cells.…”
Section: Discussionmentioning
confidence: 87%
“…In spite of the overexpression of sphingosine kinase, the sensitivity of Jaspine B varied over 12.7-fold and MBA-MD-231 cells were resistant to it. It was hypothesized that the differential sensitivity of different cancer cells to Jaspine B could be due to the differences in the cellular accumulation of Jaspine B as efflux pumps such as P-glycoprotein and BCRP have often been obstacles to cancer chemotherapy by decreasing the cellular accumulation of structurally diverse cancer drugs in various cancers [1,21]. Indeed, the cellular accumulation could be a factor responsible for the differential cytotoxic effects of Jaspine B, which was demonstrated by the significant reciprocal correlation between EC50 values and the intracellular levels of Jaspine B in different cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of efflux pumps in Jaspine B transport As the overexpression of P-gp in MDA-MB-231 and 786-O cells has been reported to be related to resistance to anti-cancer drugs and P-gp was highly expressed in 786-O cells but not in MCF-7 cells [1,21], the effect of P-gp on the efflux of Jaspine B, as well as its ability to modulate the intracellular concentration of Jaspine B was investigated.…”
Section: Methodsmentioning
confidence: 99%
“…MiRNA mediated P-gp inhibition and drug resistance reversal seem to be dose-dependent, as seen with colorectal adenocarcinoma and breast cancer cell lines [135,136] . For example, Bao et al [136] reported that P-gp expression could be reduced with miR-298 and reversed doxorubicin resistance in breast cancer cells in a dosedependent fashion.…”
Section: The Role Of Micrornas In P-gp Modulationmentioning
confidence: 99%
“…For example, Bao et al [136] reported that P-gp expression could be reduced with miR-298 and reversed doxorubicin resistance in breast cancer cells in a dosedependent fashion. In vivo studies also report that miR-873 elicits a dose-dependent response, measured by tumor growth inhibition and cisplatin sensitization in previously resistant cell lines [122] .…”
Section: The Role Of Micrornas In P-gp Modulationmentioning
confidence: 99%